Sigorta Sektörü Sorunları Yoğun Bakım Gerektiriyor - (:unkn) unknown (My University, 2002)
0

Insurance activities are of vital importance to societies and economies in terms of their functions. The activities of Turkish insurance sector stay far behind the level of development of the country and rank the last among other countries analyzed in the international comparisons. The problems are well known and it is not difficult to solve them. That's why the sector, the society and the economy are being harmed. Today, there is an urgent need for a soluation to be problems of the insurance sector in order for both our economy to maintain a stable growth and for our people to lead a peaceful life by guaranteeing their risks.